Calvatia rugosa: Epigeous Puffball Mushroom Reported from West Java - Hermawan, Rudy; Putra, Ivan Permana (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2021)
Calvatia is known as one of epigeous puffball. It is classified in Basidiomycota division and Lycoperdaceae Family. This research aimed to characterize the Calvatia species based on morphological data. Fruiting bodies of Calvatia were grown on the grass with single colony and sometimes gregarious manner.Fruiting bodies of Calvatia were collected, observed, and preserved using FAA. Fruiting bodies were collected for immature and mature stages.The particular Calvatia Â looked like pear-shaped or puffball-shaped and cream to brownish outside. The basidiospores are produced in a gasterothecium. The immature fruiting body has the brown to yellow gasterothecium. The mature fruiting body has the yellow to brown colour. The gasterothecium bore the basidiospore like a dust. Basidiospore is finely globose and free of ornament. The specimen was identified as Calvatia rugosa.